Primary Brainstem Hemorrhage: A Review of Prognostic Factors and Surgical Management - Chen, Danyang; Tang, Yingxin; Nie, Hao; Zhang, Ping; Wang, Wenzhi; Dong, Qiang; Wu, Guofeng; Xue, Mengzhou; Tang, Yuping; Liu, Wenjie; Pan, Chao; Tang, Zhouping (Frontiers in Neurology, 2021)
Primary brainstem hemorrhage (PBSH) is the most fatal subtype of intracerebral hemorrhage and is invariably associated with poor prognosis. Several prognostic factors are involved, of which the two most predominant and consistent are the initial level of consciousness and hemorrhage size. Other predictors, such as age, hyperthermia, and hydrocephalus, are generally not dependable indicators for making prognoses. Scoring systems have now been developed that can predict mortality and functional outcomes in patients suffering from PBSH, which can thus guide treatment decision-making. A novel grading scale, entitled “the new primary pontine hemorrhage (PPH) score,” represents the latest approach in scoring systems. In this system, patients with a score of 2–3 points appear to benefit from surgical management, although this claim requires further verification. The four main surgical options for the treatment of PBSH are craniotomy, stereotactic hematoma puncture and drainage, endoscopic hematoma removal, and external ventricular drainage. Nevertheless, the management of PBSH still primarily involves conservative treatment methods and surgery is generally not recommended, according to current practice. However, the ongoing clinical trial, entitled Safety and Efficacy of Surgical Treatment in Severe Primary Pontine Hemorrhage Evacuation (STIPE), should provide additional evidence to support the surgical treatment of PBSH. Therefore, we advocate the update of epidemiological data and re-evaluation of PBSH treatment in a contemporary context.